Data from: To grunt or not to grunt: factors governing call production in female olive baboons, Papio anubis - Silk, Joan B.; Roberts, Eila R.; Staedele, Veronika; Strum, Shirley C.; Städele, Veronika (Dryad, 2018)
Vocal signals often play an important role in synchronizing the activities
of group members, coordinating decisions about when and where to travel,
and facilitating social interactions in which there are potential
conflicts of interest. In chacma baboons, Papio ursinus, low amplitude
grunts facilitate nonaggressive social interactions and reconcile
conflicts. Grunts seem to function as signals of benign intent and reduce
uncertainty about the signaler's subsequent behavior. Here, we
replicate and extend these findings in another species of savanna baboons,
the olive baboon, Papio anubis. As in chacma baboons, female olive baboons
are more likely to grunt as they approach lower ranking females than as
they approach higher ranking females and are less likely to grunt as they
approach their own mothers and daughters than as they approach other
females. Taken together, these data support the hypothesis that baboons
modify their call production for different listeners in different social
contexts, and support the view that the mechanisms underlying call
production may overlap with the mechanisms underlying call perception.
Data supporting analysesDryad.xlsx
Keywords: replication; grunts; signals of benign intent; baboon; Papio anubis